At War, but Far From The Front: Crashes, Disasters, and The Newfoundland Airport - Daly, Lisa M. (Newfoundland and Labrador Studies, 2023)
The Newfoundland Airport, in what became Gander, Newfoundland and Labrador, was an area of both conflict and logistics during the Second World War. The airbase served roles as both a stopping point for aircraft to be ferried from production facilities in North America to the war theatre overseas, for convoy escorts and U-boat hunting, as well as mundane deliveries of people and equipment from Canada and the United States. During the war, the airbase was very active, with thousands of aircraft using the runways, and there were aircraft lost, whichremain on the landscape around Gander. For those serving at the Newfoundland Airport, the war may have been ever-present, but at the same time distant; there was no active battle at the airbase, but there were casualties of war. Those who died were filling combat and logistical roles, and post-war rebuilding efforts. Accidents occurred due to mechanical malfunctions, the weather, and human error. Using historical records and archaeological site inventories, this paper will examine the role of this non-combatant space and advocate that the material cultureof aircraft crash sites be conceptualized within the larger context of aviation infrastructure. The result will expand our understanding of the impact and tragedy of war for the airbase at Gander, and for Newfoundland and Labrador.